1‐Stearoyl‐2‐docosahexaenoyl‐phosphatidic acid interacts with and activates Praja‐1, the E3 ubiquitin ligase acting on the serotonin transporter in the brain. Issue 11 (19th March 2020) - Lu, Qiang; Murakami, Chiaki; Murakami, Yuki; Hoshino, Fumi; Asami, Maho; Usuki, Takako; Sakai, Hiromichi; Sakane, Fumio
Abstract : Serotonin transporter (SERT) is involved in serotonergic system regulation and in the pathophysiology/therapeutics of serotonin‐/SERT‐related diseases such as obsessive‐compulsive disorder, depression, autism, and schizophrenia. We recently revealed that diacylglycerol (DG) kinase (DGK) δ induces ubiquitination/degradation of SERT in a DGK activity‐dependent manner through Praja‐1 E3 ubiquitin‐protein ligase. However, it is still unclear how Praja‐1 activity is regulated by DGKδ. Here, we reveal that 1‐stearoyl‐2‐docosahexaenoyl (18:0/22:6)‐phosphatidic acid (PA) and 18:0/22:6‐DG are simultaneously decreased and accumulated, respectively, in the DGKδ‐knockout mouse brain, indicating that DGKδ selectively phosphorylates 18:0/22:6‐DG to generate 18:0/22:6‐PA. Moreover, we find that 18:0/22:6‐PA selectively binds to Praja‐1 and enhances its activity. These results strongly suggest that 18:0/22:6‐PA generated by DGKδ activates Praja‐1 to degrade SERT in the brain. Abstract :